(2r-3)/7+(3/7)=(-r/3)

Simple and best practice solution for (2r-3)/7+(3/7)=(-r/3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2r-3)/7+(3/7)=(-r/3) equation:


r in (-oo:+oo)

(2*r-3)/7+3/7 = -r/3 // + -r/3

(2*r-3)/7-(-r/3)+3/7 = 0

(2*r-3)/7+(1/3)*r+3/7 = 0

(2*r-3)/7+r/3+3/7 = 0

(3*(2*r-3))/(3*7)+(7*r)/(3*7)+(3^2)/(3*7) = 0

3*(2*r-3)+7*r+9 = 0

13*r-9+9 = 0

13*r = 0

(13*r)/(3*7) = 0

(13*r)/(3*7) = 0 // * 3*7

13*r = 0

13*r = 0 // : 13

r = 0

r = 0

See similar equations:

| 8y+3=6y+13 | | 4t+3(x-9)=12 | | ln(4x+3)+ln(2)=3.2 | | 2a+45-2.5(4a+21)=(a+2a+44) | | Y-7=2x+y-15 | | 7/9x+8y-8/3x-1/5y | | -.34x+12=-x+4 | | (x-8)/5+(8/5)=(-x/3) | | (4x+6)/2=15 | | (4t+1)/3=(t+5)/6+(t-3)/6 | | 4x+6/2=15 | | 68+65+x+x=360 | | 3x+3x+3x+3x=360 | | 10z+5=2(5z+8)-12 | | 59=5.6m-2.6 | | v+12-30=2 | | 5+3u-7=20 | | 5c-7=15 | | 4x-4=7x-6 | | 8+f-12=2 | | 2(x-7)-3(x+2)+4(x+1)-2=0 | | 7a=4a-9 | | 2x^2-(4-x^2)=6x-4 | | 12z+4=2(2x-7) | | (4x-4/x-7)(3x+5/x-1) | | 5n=53.2-2.6n | | 10+.06x=0 | | 11=7+4w | | 7y+8/2=4 | | 60+60+x+x=360 | | -8+4v=16 | | 60+60+x+x= |

Equations solver categories